Abnormal CFTR Affects Glucagon Production by Islet α Cells in Cystic Fibrosis and Polycystic Ovarian Syndrome - Huang, Wen Qing; Guo, Jing Hui; Yuan, Chun; Cui, Yu Gui; Diao, Fei Yang; Yu, Mei Kuen; Liu, Jia Yin; Ruan, Ye Chun; Chan, Hsiao Chang (Frontiers in Physiology, 2017)
Glucagon, produced by islet α cells, functions to increase blood glucose. Abnormal glucose levels are often seen in cystic fibrosis (CF), a systematic disease caused by mutations of the CF transmembrane conductance regulator (CFTR), and in polycystic ovarian syndrome (PCOS), an endocrine disorder featured with hyperandrogenism affecting 5–10% women of reproductive age. Here we explored the role of CFTR in glucagon production in α cells and its possible contribution to glucagon disturbance in CF and PCOS. We found elevated fasting glucagon levels in CFTR mutant (DF508) mice compared to the wildtypes. Glucagon and prohormone convertase 2 (PC2) were also upregulated in CFTR inhibitor-treated or DF508 islets, as compared to the controls or wildtypes, respectively. Dihydrotestosterone (DHT)-induced PCOS rats exhibited significantly lower fasting glucagon levels with higher CFTR expression in α cells compared to that of controls. Treatment of mouse islets or αTC1-9 cells with DHT enhanced CFTR expression and reduced the levels of glucagon and PC2. The inhibitory effect of DHT on glucagon production was blocked by CFTR inhibitors in mouse islets, and mimicked by overexpressing CFTR in αTC1-9 cells with reduced phosphorylation of the cAMP/Ca2+ response element binding protein (p-CREB), a key transcription factor for glucagon and PC2. These results revealed a previously undefined role of CFTR in suppressing glucagon production in α-cells, defects in which may contribute to glucose metabolic disorder seen in CF and PCOS.